Law, medicine & health care : a bibliography - Ziegenfuss, James T. (New York, N.Y. : Facts on File Publications, 1984)
Over 3500 references to literature (mostly journal articles) published during the 1970's and 1980's. Broadly arranged under specialties, medical care organization, medical services, and legal processes. Classified order. Entries give bibliographical information. Contains lists of journals and law firms.
Second letter i in cover title represented by caduceus.
Keywords: Jurisprudence